Smart Building Application in Revitalization of Historic Buildings Case Study: The Museum Bahari, Jakarta - Kadeli, Kadeli; Eni, Sri Pare; Marpaung, Charles O.P (CV. Publikasi Indonesia, 2025)
Historical buildings are cultural heritages that require preservation while adapting to modern demands. The Museum Bahari in Jakarta faces challenges in revitalizing its historical architectural elements while integrating adaptive technologies. This research examines the application of smart building systems in revitalizing the museum with minimal intervention to maintain historical integrity. A descriptive qualitative method is used, involving condition analysis, identification of smart technologies, and strategy development. Data collection includes observation, literature review, and case study analysis. Findings indicate that technologies such as humidity sensors, adaptive lighting, and environmental monitoring can enhance building performance and visitor experience without compromising heritage values. This study recommends placing devices in non-structural areas, integrating energy management with conservation needs, and using real-time monitoring systems. These strategies align with heritage conservation principles. The study concludes that smart building technology with minimal intervention offers a sustainable solution for revitalizing historic buildings like the Museum Bahari while enhancing functionality and relevance in the modern era.